Pathogenesis and Treatment of T-Large Granular Lymphocytic Leukemia (T-LGLL) in the Setting of Rheumatic Disease - Couette, Nina; Jarjour, Wael; Brammer, Jonathan E.; Simon Meara, Alexa (Frontiers in Oncology, 2022)
A complex relationship exists between rheumatic diseases and cancer. This delicate balance between chronic inflammation and malignant cell transformation in hematologic neoplasms has been observed, but is not well defined. Large Granular Lymphocyte (LGL) leukemia is at the intersection of a clonal lymphoproliferative disease, chronic inflammation, and autoimmunity. The association between rheumatoid arthritis (RA) and the spectrum of Felty’s Syndrome is well-known. Other rheumatic disorders have been reported including systemic lupus erythematosus (SLE), Sjogren’s Syndrome (SS), vasculitis, Behcet’s Disease (BD) and systemic sclerosis. The association between T-LGLL and rheumatic disease pathogenesis has been hypothesized, but has not yet been fully understood. Components of a shared pathogenesis includes chronic antigen stimulation, JAK-STAT pathway activation and overlap of various cytokines. We will summarize current knowledge on the molecular understanding between T-LGLL and rheumatic disease. There are many potential areas of research to help meet this need and lead to development of targeted therapeutic options.